Improving Early Childhood Educators' Communication Skills for Optimal Child Growth and Development - Jimi Harianto; Fiky Nurrohmah; Revalina Ardinda (South Sulawesi Education Development (SSED), 2025)
Purpose: The causal relationship between teacher communication skills and early childhood developmental outcomes has been a central focus of empirical inquiry in early childhood education literature. While effective teacher-child communication is widely recognized as a critical driver of children's cognitive, linguistic, and socio-emotional growth, a comprehensive synthesis of existing evidence remains necessary to establish a solid theoretical foundation for the design of teacher training programs. This literature review aims to synthesize empirical evidence from previous research on the impact of improving early childhood teachers' communication skills on key developmental indicators in early childhood. The study's significance lies in providing an evidence-based framework to inform the development of communication-competency-focused teacher professional development initiatives. Methodology: This study employed a systematic literature review approach, analyzing peer-reviewed empirical research published between 2020 and 2025. Data sources included major indexed academic databases such as Scopus, Web of Science, ERIC, and Google Scholar. Relevant journal articles employing both qualitative and quantitative methodologies were selected using predetermined keywords related to teacher communication skills and early childhood development. A total of 25 articles meeting the inclusion criteria were identified, critically appraised, and synthesized thematically to identify consistent patterns regarding communication training interventions, pedagogical strategies, and their associated child developmental outcomes. Results : The thematic synthesis of the 25 selected research articles reveals consistent and converging findings. The literature indicates that structured training interventions including coaching, microteaching, reflective practice, and video-based professional learning significantly improve teachers' responsive and instructional communication competencies. Based on evidence from the reviewed studies, these improvements are strongly correlated with measurable child progress across multiple developmental domains, particularly vocabulary acquisition, expressive and receptive language skills, social competence, active participation in classroom interactions, and emotional regulation. Studies further suggest that the quality of teacher-child verbal interaction, characterized by open-ended questioning, contingent responsiveness, and extended discourse, serves as a key mediating factor in facilitating positive developmental outcomes. Conclusions: This review establishes that there is strong, consistent scientific evidence in the literature linking improvements in early childhood teachers' communication skills to more positive child developmental outcomes across cognitive, linguistic, and socio-emotional domains. The findings underscore the critical need for evidence-based, explicitly communication-competency-focused approaches in teacher professional development programs. Recommendations are provided for policymakers, teacher educators, and early childhood institutions to prioritize sustained, practice-oriented communication training as a foundational component of professional development frameworks, ultimately fostering higher-quality teacher-child interactions that support children's holistic development during the critical early years.